2018
DOI: 10.3802/jgo.2018.29.e32
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance in ovarian cancer: exploiting cancer stem cell metabolism

Abstract: Ovarian cancer is most deadly gynecologic malignancies worldwide. Chemotherapy is the mainstay treatment for ovarian cancer. Despite the initial response is promising, frequent recurrence in patients with advanced diseases remains a therapeutic challenge. Thus, understanding the biology of chemoresistance is of great importance to overcome this challenge and will conceivably benefit the survival of ovarian cancer patients. Although mechanisms underlying the development of chemoresistance are still ambiguous, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 81 publications
0
103
1
Order By: Relevance
“…It has been demonstrated that enhanced glucose uptake and improved aerobic glycolysis are capable to induce the intrinsic or acquired resistance to chemotherapy in several tumor cells such as breast (125), or ovarian (107). Several key glycolytic enzymes and glucose transporters inhibitors are currently in preclinical or clinical development to counteract resistance to chemotherapeutic drugs (100,107,(126)(127)(128)(129). Some reports proposed that aerobic glycolysis is an important pathway for colorectal cancer (CRC) development.…”
Section: Targeting Glucose Metabolismmentioning
confidence: 99%
“…It has been demonstrated that enhanced glucose uptake and improved aerobic glycolysis are capable to induce the intrinsic or acquired resistance to chemotherapy in several tumor cells such as breast (125), or ovarian (107). Several key glycolytic enzymes and glucose transporters inhibitors are currently in preclinical or clinical development to counteract resistance to chemotherapeutic drugs (100,107,(126)(127)(128)(129). Some reports proposed that aerobic glycolysis is an important pathway for colorectal cancer (CRC) development.…”
Section: Targeting Glucose Metabolismmentioning
confidence: 99%
“…Resistance to chemotherapy is a contributing factor to mortality in ovarian cancer 17 , 18 . The mechanisms of chemoresistance in ovarian cancer are unclear but are thought to involve both intrinsic and acquired molecular responses 19 . Intrinsic resistance involves the presences of cancer stem cells whereas acquired resistance involves the genetic and epigenetic alteration of genes in response to repetitive chemotherapy 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is useful to kill small amounts of tumor cells that may still exist after surgery, or to shrink large tumors to make surgery easier. While approximately 75 % of patients initially respond to the chemotherapy, most of them relapse with chemoresistance which results in treatment failure and causes over 90 % of deaths [3]. Second-line chemotherapies are often required, however, in contrast to first-line chemotherapy, the anticancer effect of second-line chemotherapies is usually bad.…”
Section: Introductionmentioning
confidence: 99%